Mapping the sources of tension and the insterests of regional powers in Afghanistan and Pakistan. (CIDOB Policy Research Project, 2012)
The document schematically summarizes policy research findings on the sources of tension with regional implications that affect Afghanistan and Pakistan; and identifies the interests of, and related “red lines” for, the five main implicated regional powers: India, Iran, Russia, China and Saudi Arabia.